(untitled) (Research, Society and Development, 2021)
Objective: To analyze in the literature studies addressing pressure injuries in bedridden patients with advanced age. Method: This is an integrative literature review, of articles published from 2016 to 2019, in the following databases: LILACS, SciELO and MEDLINE. The search terms were: Pressure injury; Nursing care; Elderly, published in English and Portuguese. 165 articles were identified with themes relevant to the objective of the study. After reading in full, 20 articles were selected according to the distribution of the publications selected in the databases of the chosen articles. Results: Such publications emphasize nursing care for pressure injuries in elderly patients, especially in the prevention of these injuries, which are most often recurrent in bedridden elderly. Although the various causes of LPP are recognized, and multidisciplinary care is of utmost importance for health care, it is a fact that the nursing team is responsible for direct and continuous care for patients, which gives it a prominent role in preventing this. problem. Conclusion: It showed through the analysis of selected productions, that pressure injuries are more common in bedridden and elderly patients due to their vulnerability. This occurs through the aging process, in which there are several changes in the skin in which its support structures associated with other body systems make the skin more vulnerable to pressure, shear and friction. Nursing is essential in preventive measures, in order to reduce and control damage from pressure injuries.